2022
DOI: 10.1108/bij-12-2021-0749
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing customer satisfaction, personnel satisfaction and company reputation with total quality management: combining traditional and new views

Abstract: PurposeThis study investigates the effect of total quality management (TQM) on customer satisfaction, personnel satisfaction and company reputation.Design/methodology/approachThe study results rely on a structured survey conducted among an extensive sample of Finnish SMEs. In addition to the examination of the relationship between TQM and company performance in terms of customer satisfaction, personnel satisfaction and company reputation, the study takes a view on the possible effects of the industry, the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
(203 reference statements)
1
8
0
Order By: Relevance
“…Due to cross-sectional nature of our research design, we used multiple approaches to minimise common method bias (CMB) and we are confident that it was not an issue for our study. The potential problem of common method bias was reduced through procedural methods such as developing variables through exhaustive review of literature, maintaining anonymity, providing thinking time to respond to the items of the questionnaire (Lepist€ o et al, 2022;Memon et al, 2020) as well through statistical methods where the variance inflation factor (VIF) was measured along with the measurement properties of the model to nullify the impact of common bias (Qalati et al, 2021). Further, we validated the items in consultation with four senior HR managers and three researchers in cross-cultural HRM field before conducting the survey.…”
Section: Common Methods Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to cross-sectional nature of our research design, we used multiple approaches to minimise common method bias (CMB) and we are confident that it was not an issue for our study. The potential problem of common method bias was reduced through procedural methods such as developing variables through exhaustive review of literature, maintaining anonymity, providing thinking time to respond to the items of the questionnaire (Lepist€ o et al, 2022;Memon et al, 2020) as well through statistical methods where the variance inflation factor (VIF) was measured along with the measurement properties of the model to nullify the impact of common bias (Qalati et al, 2021). Further, we validated the items in consultation with four senior HR managers and three researchers in cross-cultural HRM field before conducting the survey.…”
Section: Common Methods Biasmentioning
confidence: 99%
“…Due to cross-sectional nature of our research design, we used multiple approaches to minimise common method bias (CMB) and we are confident that it was not an issue for our study. The potential problem of common method bias was reduced through procedural methods such as developing variables through exhaustive review of literature, maintaining anonymity, providing thinking time to respond to the items of the questionnaire (Lepistö et al. , 2022; Memon et al.…”
Section: Methodsmentioning
confidence: 99%
“…These are customer focus, process management, supplier quality involvement and cross-functional product design. Besides, the most recent research work carried-out by Lepist€ o et al (2022) identified the Nobel approaches to TQM dimensions: risk management, stakeholder management, digitalization and system deployment in addition to the traditional approach to TQM dimensions such as, management/leadership, data and reporting, customer and personnel focus, process management, products/service improvement, procurement and materials, continuous improvement. Dametew et al (2020) also identified three SCM unique practices, namely procurement; distribution and material handling; internal logistics management.…”
Section: Ijqrm 4010mentioning
confidence: 99%
“…The joint implementation of the aforementioned initiatives is seen as a natural alignment through their similar operations management approach (Nandurkar et al, 2014;Hailu et al, 2018a;Sisay et al, 2021). For example, LM refers to a long-term management philosophy that helps the organizations to identify and eliminate waste through CI and respect for people (Liker, 2004;Klein et al, 2022); TQM refers to a management philosophy which builds its objective of organizational effectiveness on the following interconnected factors: quality, people, organizations and management (Lepist€ o et al, 2022); SCM is the relationship management from upstream to downstream or from suppliers to consumers to provide more value to customers and reduce supply chain costs (Hwihanus et al, 2022); IM is the operationalization of creative potential with a commercial and social motive by implementing new adaptive solutions that create value, harness new technology or invention, contribute to competitive advantage and economic growth (Singh and Aggarwal, 2022); LSS is a powerful methodology or strategy which promoting quality improvement to achieve organization's operational excellence, waste reduction and process improvements (Daniyan et al, 2022). From this perspective, synthesizing these paradigms into an integrated framework results in the combination of the best of the five programs as the latest generation improvement technique which IJQRM 40,10 integrates human and strategic (or technical) elements into a program that sequences improvement to an overall approach for industrial performance and business growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation